Strategic Insights into Cash Waqf Collection: An Analytical Network Approach - Indirwan, Syanisma Khansa; Siti Inayatul Faizah (Jurnal Ekonomi Syariah Teori dan Terapan, 2024)
This study was conducted to examine the problems and priority solutions to optimize the collection of cash waqf in East Java that can be implemented in the short and long term. The method used is quasi qualitative using the Analytical Network Process (ANP) method and analyzed using Benefit, Opportunity, Cost, and Risk (BOCR). The data was processed using Super Decision 2.10 software. There are several findings in the results of this study. First, the highest priority in optimizing cash waqf collection is the nazir aspect (0.53628), the wakif aspect (0.293), and finally the regulator aspect (0.17072). Second, based on short-term analysis, the main solution priority is transparency of financial reports and institutional performance (0.29476). Meanwhile, based on long-term analysis, the main solution priority is the socialization and education of cash waqf (0.16748). These findings emphasize the important role of nazir to be able to improve their competence in digital marketing to increase the collection of cash waqf at Waqf Institutions in East Java.